Communication and Sustainability: The unfolding of the sustainability narrative in the organizational context - Tomiotto, Maria Fernanda (2019)
Sustainability, resulting from an interactive process, based on people and their narratives, impacts organizational behavior in different contexts and time-spaces. This article advances by studying this phenomenon from the communication’s perspective, which proposes the consideration of different visions for the construction of senses. In a procedural and dynamic view, guided by the sensemaking perspective, this study question: In what ways did the sustainability narratives manifest in a company recognized as sustainable? The analysis unit, Itaipu Binacional, has been study in a qualitative, descriptive and documentary approach, using narrative’ analysis as a technique. We sought answers in the articulations and movements registered by the documents that contributed to construct the sustainability’s narrative in the organization. We identified three moments that demonstrate the organization's sustainability narrative, discussed throughout the paper. Despite the peculiarities of each moment, we identified the predominance of a sustainability orientation aligned with the reform.